MONITORING OF RESEARCH ON THE CHEMICAL COMPOSITION OF WHITE ROOT CROPS - S. Lehnert; V. Zaytseva; A. Dubinina; M. Mardar; T. Kuklina; O. Cherevko; T. Letuta; L. Tatar (Harčova Nauka ì Tehnologìâ)
Recently, there has been an increase in demand for white root crops due to their dietary properties. The problem that is being solved in this work is to determine the possibility of overcoming the deficiency of essential substances in nutrition through the use of white root vegetables, namely parsley, celery and parsnips. The methodology adopted for this study is based on the analysis and synthesis of data from literary sources (articles in scientific publications, monographs, etc.). The research results into the chemical composition of white root crops by many scientists of the universe are given. It is shown that they are a source not only of easily digestible carbohydrates, ballast and mineral substances, but also of functional ingredients – phytosterols, phenolic compounds, phytoalexins, phthalides, bioactive aliphatic polyacetylenes. Thanks to this, white root crops have very good medicinal properties – from a positive effect in obesity, neuroses to the treatment of atherosclerosis, prostate adenoma. They have antibacterial, antimicrobial, anti-inflammatory, anti-cancer and antioxidant effects. The problem of accumulation of contaminants by white root crops, which have a toxic effect on the human body, is considered. The species, variety, and morphological specificity of the accumulation of contaminants by white root crops, as well as the influence of the area of their cultivation, the type of crop and its variety, as well as the tissue specificity of the accumulation of all chemical elements on this process are shown. Data on the high content of oxalic acid and its salts, nitrates and salts of heavy metals in white root crops are presented. The necessity of conducting scientific research on the search for new, more effective methods of processing raw materials has been proven. The prospect of using white root crops for the production of special purpose products after their detoxification has been proven.